Spraying solo or mixed glyphosate after different ready-mixed solution storage periods - Saul Jorge Pinto de Carvalho; Débora Fernanda Oliveira Batista; Jonathan Miguel Matoso; Ludimila Justina Ferreira da Silva; Michele de Souza (Revista Agrogeoambiental)
The continuous need to use tank mixtures of herbicides for managing hard-to-control weeds, particularly volunteer soybean in second-crop corn, motivated this study. Therefore, this work was developed in order to evaluate the efficacy of glyphosate (applied solo or in mixtures with 2,4-D or atrazine) following various storage periods of the ready-mixed spray solution. To this end, five greenhouse experiments were carried out from 2015 to 2017, three using an application volume of 240 L ha−1 and two with a reduced volume of 120 L ha−1. Treatments followed a factorial design (5×3) + 1, with five storage durations for the ready-mixed spray solution: 1, 24, 48, 96, and 168 hours; three herbicide treatments: glyphosate solo (720 g a.e. ha−1), glyphosate + atrazine (720 + 1,500 g a.e. ha−1), and glyphosate + 2,4-D (720 + 670 g a.e. ha−1); plus, checkplots without application. The bioindicators used were morning glory (Ipomoea triloba), sourgrass (Digitaria insularis), and volunteer Roundup Ready soybean. Overall, the storage duration of the ready-mixed herbicide solution had no significant impact on herbicide efficacy. Glyphosate solo provided the best control of sourgrass; mixtures of glyphosate with atrazine or 2,4-D most effectively controlled morning glory, and the glyphosate + atrazine and glyphosate + 2,4-D treatments achieved the highest control of volunteer transgenic soybean. Minor indications of antagonism were observed in the mixtures of glyphosate + atrazine and glyphosate + 2,4-D.